Importance of vaccine action and availability and epidemic severity for delaying the second vaccine dose - Berec, Luděk; Levínský, René; Weiner, Jakub; Šmíd, Martin; Neruda, Roman; Vidnerová, Petra; Suchopárová, Gabriela (Scientific reports, 2022)
Following initial optimism regarding potentially rapid vaccination, delays and shortages in vaccine supplies occurred in many countries during spring 2021. Various strategies to counter this gloomy reality and speed up vaccination have been set forth, of which the most popular has been to delay the second vaccine dose for a longer period than originally recommended by the manufacturers. Controversy has surrounded this strategy, and overly simplistic models have been developed to shed light on this issue. Here we use three different epidemic models, all accounting for then actual COVID-19 epidemic in the Czech Republic, including the real vaccination rollout, to explore when delaying the second vaccine dose by another 3 weeks from 21 to 42 days is advantageous. Using COVID-19-related deaths as a quantity to compare various model scenarios, we find that the way of vaccine action at the beginning of the infection course (preventing infection and symptoms appearance), mild epidemic and sufficient vaccine supply rate call for the original inter-dose period of 21 days regardless of vaccine efficacy. On the contrary, for the vaccine action at the end of infection course (preventing severe symptoms and death), severe epidemic and low vaccine supply rate, the 42-day inter-dose period is preferable, at any plausible vaccine efficacy.
Keywords: vakcinace; lidé; Vaccination; SARS-CoV-2; vakcíny; COVID-19 Vaccines; vakcíny proti COVID-19; COVID-19; Vaccines; Humans